Mini review on collagens in normal skin and pathological scars: current understanding and future perspective - Zhou, Claire Jing; Guo, Yuan (Frontiers in Medicine, 2024)
Pathological scar tissues are characterized by the presence of overabundant collagens whose structure and organization are also different from those in unwounded skin. This causes scar tissues to lose some functions performed by normal skin, and currently, there are no effective measures to prevent scar formation. Inflammation has been shown to modulate fibroblast proliferation, differentiation, and function, hence collagen production and organization. In this minireview, we provide an overview of the current understanding of collagen, specifically collagen type I and III which are main collagens in skin, structure and fibre formation and highlight their differences between normal skin and pathological scars. We discuss the role that cytokines play in modulating fibroblast function. We also identify some potential research directions which could help to further our understanding of the complex and dynamic wound healing and scar formation process.